Critical discourse in Victorian literature in works: Vanity Fair and Great Expectations - Boháčová, Lucie (Univerzita Pardubice, 2013)
The main purpose of this paper is to provide an analysis of the novels Great Expectations by Charles Dickens and Vanity Fair by William Makepeace Thackeray which date back to the Victorian period and portray typical values of Victorian society. In the theoretical part of the paper the historical background of the Victorian period is contextualized. The second part covers an analysis of the plays with special attention being paid to Victorian values which both authors criticized. These values of both novels are then compared.
Kritický pohled na viktoriánskou literaturu v dílech: Jarmark marnosti a Nadějná očekávání
Keywords: Nadějné vyhlídky; Jarmark marnosti; Dickens, Charles; Thackeray, William Makepeace; Viktoriánské období; kritika; Great Expectations; Vanity Fair; Victorian period; criticism